2015
DOI: 10.1111/aas.12549
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of neuromuscular block with sugammadex: a comparison of the corrugator supercilii and adductor pollicis muscles in a randomized dose–response study

Abstract: Sugammadex 4 mg/kg was required to reverse a moderate rocuronium-induced neuromuscular block when the corrugator supercilii muscle is used for monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…In children aged 2 to 5 years, PTC 1 can be detected in 29.8 min even after a high dose of 1 mg•kg −1 of rocuronium. 12) In the light of the fact that the ED 95 of rocuronium in infants is significantly lower than that in older children (0.25 vs. 0.41 mg•kg −1 ), 11) the plasma concentration or number of molecules of rocuronium should be smaller in infants and younger children at the same PTC level. Since one sugammadex molecule encapsulates one rocuronium molecule, it is therefore speculated that a smaller dose of 2 mg•kg −1 of sugammadex may reverse a deep rocuronium-induced neuromuscular block in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In children aged 2 to 5 years, PTC 1 can be detected in 29.8 min even after a high dose of 1 mg•kg −1 of rocuronium. 12) In the light of the fact that the ED 95 of rocuronium in infants is significantly lower than that in older children (0.25 vs. 0.41 mg•kg −1 ), 11) the plasma concentration or number of molecules of rocuronium should be smaller in infants and younger children at the same PTC level. Since one sugammadex molecule encapsulates one rocuronium molecule, it is therefore speculated that a smaller dose of 2 mg•kg −1 of sugammadex may reverse a deep rocuronium-induced neuromuscular block in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that this requirement would be equally important if reversal is accomplished with sugammadex, because the current dose recommendations were developed based on the evaluation of the adductor pollicis response and are not applicable when reversal is guided by eye-muscle monitoring. 39 Previous research has demonstrated that administering neostigmine at a TOF count of 4 is significantly more likely to yield satisfactory and timely reversal compared with a lower TOF count. However, it is also clear from previous research that a successful reversal is not guaranteed even when the spontaneous recovery has progressed to a TOF count of 4.…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports and few clinical studies have evaluated the efficacy and safety of sugammadex in elderly patients 38 49 ( Table 3 ). McDonagh et al conducted a parallel-group, comparative, open-label study evaluating sugammadex 2 mg/kg administered for reversal of moderate rocuronium-induced NMB in 150 patients undergoing intravenous or inhalational general anesthesia.…”
Section: Pharmacology In the Elderlymentioning
confidence: 99%